2005
DOI: 10.1124/jpet.104.077891
|View full text |Cite
|
Sign up to set email alerts
|

Sulfone Metabolite of Fipronil Blocks γ-Aminobutyric Acid- and Glutamate-Activated Chloride Channels in Mammalian and Insect Neurons

Abstract: Fipronil sulfone, a major metabolite of fipronil in both insects and mammals, binds strongly to GABA receptors and is thought to play a significant role in poisoning by fipronil. To better understand the mechanism of selective insecticidal action of fipronil, we examined the effects of its sulfone metabolite on GABA-and glutamate-activated chloride channels (GluCls) in cockroach thoracic ganglion neurons and on GABA A receptors in rat dorsal root ganglion neurons using the whole-cell patch-clamp technique. Fip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 29 publications
1
62
0
11
Order By: Relevance
“…Orr et al (2009) chloride channels in insects (ZHAO et al, 2005). Also, it acts in the reproductive process by altering both the structure and function of germinative cells of R. sanguineus females (OLIVEIRA et al, 2009).…”
Section: Macdonald (1995)mentioning
confidence: 99%
“…Orr et al (2009) chloride channels in insects (ZHAO et al, 2005). Also, it acts in the reproductive process by altering both the structure and function of germinative cells of R. sanguineus females (OLIVEIRA et al, 2009).…”
Section: Macdonald (1995)mentioning
confidence: 99%
“…The fact of chemical injury to the CNS can change the phases of acquisition, consolidation and recall of the memory [11] contributes to raise questions about GABAergic system involvement. In this sense it was recently demonstrated that reduction of GABA in the prefrontal cortex caused a delay in the activities done by monkeys [12][13][14].…”
Section: Introductionmentioning
confidence: 97%
“…However, it was unlear whether the conversion of fipronil to its sulfone represented detoxication in mammals and insects. Fipronil sulfone blocked both slowand fast-desensitizing GluCls (Zhao et al, 2005). The IC 50 for slow-and fast-desensitizing currents were calculated to be 8.5 ± 0.4 nM (n = 4) and 25 ± 2 nM (n = 4), respectively.…”
Section: Glutamate-activated Chloride Channel: Unique Chemical Targetmentioning
confidence: 99%